Clinical profile of confirmed scorpion stings in a referral center in Manaus, Western Brazilian Amazon. (November 2020) - Gomes, Jacimara Vasques; Fé, Nelson Ferreira; Santos, Hildegard Loren Rebouças; Jung, Bruna; Bisneto, Pedro Ferreira; Sachett, André; de Moura, Valéria Mourão; Mendonça da Silva, Iran; Cardoso de Melo, Gisely; Pereira de Oliveira Pardal, Pedro; Lacerda, Marcus; Sampaio, Vanderson; et al.
Abstract: Scorpion envenomations are a major public health problem in Brazil, and most medically important cases are attributable to the Tityus genus. The objective of this study is to describe the clinical and epidemiological aspects of a series of 151 cases of confirmed scorpion stings, which were treated at the hospitals of two cities in the Western Brazilian Amazon, between June 2014 and December 2019. This study shows that the genus Tityus was the most prevalent. Tityus ( Atreus ) metuendus (Pocock, 1897) was responsible for the greatest number of cases (68.2%), followed by Tityus ( Archaeotityus ) silvestris (Pocock, 1897) (14.6%). Most of the envenomations involved males (53.6%), and analysis showed a slight predominance in the group from 40 to 49 years (22.5%). The most affected body regions were feet (49.0%) and hands (31.8%). The time elapsed between the accident and medical care was ≤6 h in 92.1% of cases. Regarding clinical severity, classes I (80.8%) and II (15.9%) predominated. However, there were five (3.3%) class III cases; four for T. metuendus and one for T. silvestris . The most frequent local and systemic manifestations were, respectively, pain (84.1%), paresthesia (34.4%) and mild edema (25.8%), and nausea (9.3%) and myoclonia (8.6%). The clinical manifestations were similar among the patients stung by the different species of scorpions. There were no differences between the manifestations of envenomation caused by T. metuendus, T. silvestris and T. raquelae . For victims of T. apiacas, a higher frequency of piloerection and myoclonia was observed, and was described by the affected patients as a 'sensation of receiving an electric shock' throughout the body. No deaths were registered. The species of greatest epidemiological importance in Manaus is T. metuendus, a species that leads to clinical pictures that do not differ substantially from those observed in other Brazilian regions. T. apiacas causes neurological manifestations that differed from other Tityus species. Our findings suggest that the available antivenoms have little effectiveness when used in the treatment of envenomations by some Amazonian scorpions. Highlights: A case series of 151 confirmed scorpion envenomations from the Brazilian Amazon is presented. Tityus metuendus is the most common agent of envenomation in Manaus and the surrounding region. Severe cases of scorpion envenomations were reported. Tityus apiacas stings cause neurological manifestations not observed in envenomation by other Tityus species. Available antivenoms seem to have little effectiveness in the treatment of envenomations by some Amazonian scorpions.